Tinjauan Aspek Hukum terhadap Pelaksanaan dan Mekanisme Eksekusi Perkara Sengketa Tanah : (Studi Kasus di Pengadilan Negeri Palangkaraya) - Anisa Miftahul Firdaus; Niken Wahyuning Retno Mumpuni (CV Rewang Rencang, 2025)
This research examines the implementation of execution in land dispute cases at the Palangkaraya District Court. Execution often faces obstacles despite the existence of final and binding court decisions. The purpose of this research is to understand the legal aspects and mechanisms of execution implementation. This research uses a normative-empirical approach. The results show numerous constraints, both juridical and non-juridical, that cause low success rates in execution.